Discoloured seeds of amaranth plant infected by Alternaria alternata: physiological, histopathological alterations and fungal secondary metabolites associated or registered - Noelting, María Cristina (2016)
In the present study the aspects of discolouration that could influence both the production and consumption of amaranth were analyzed with the objectives to identify the presence of Alternaria alternata on seeds, to analyze possible changes in the anatomy of seed tissues and to detect the presence of fungal secondary metabolites. Component plating, histopathological and mycological analyses on discoloured seeds allowed i) location of propagules of A. alternata in all seminal components; ii) observation of hypertrophies in perisperm and embryo and iii) determination of several fungal secondary metabolites, mainly high concentrations of tenuazonic acid. To our knowledge, the information presented in this paper, related to physiological, histopathological changes and fungal secondary metabolites on discoloured seeds of (Amaranthus mantegazzianus syn. A. caudatus subsp. mantegazzianus (Pass) Hanelt affected by A. alternata, is the first worldwide record.